College admissions and the role of information: An experimental study - Joana Pais; Agnes Pintér; Róbert F. Veszteg (Osaka University, Institute of Social and Economic Research (ISER), 2008)
We analyze two well-known matching mechanisms-the Gale-Shapley, and the Top Trading Cycles (TTC) mechanisms-in the experimental lab in three different informational settings, and study the role of information in individual decision making. Our results suggest that-in line with the theory-in the college admissions model the Gale-Shapley mechanism outperforms the TTC mechanisms in terms of efficiency and stability, and it is as successful as the TTC mechanism regarding the proportion of truthful preference revelation. In addition, we find that information has an important effect on truthful behavior and stability. Nevertheless, regarding efficiency, the Gale-Shapley mechanism is less sensitive to the amount of information participants hold.
Keywords: C78; C91; D82; 330; experiments; information; matching; Entscheidungstheorie; Matching; Information; Test; Bildungsverhalten; Hochschule